Time Course of Acute Hip Adduction Range of Motion Changes Following Foam Rolling - Anthony D'Amico; Kevin Silva; Joseph Gallo (North American Sports Medicine Institute, 2021)
# Background With the increased popularity of foam rolling (FR), it is important to establish the exact manner in which the practice is useful. # Purpose The purpose of this study was to examine the impact of FR the iliotibial (IT) band on hip adduction range of motion (ROM) and the short-term time course of any ROM changes that may occur. # Method In a within-subject design, 34 subjects (21 female, 13 male) (female mean age 24.67 ± 8.6 yrs, height 161.4 ± 9.8 cm, mass 67.3 ± 12.3 kg; male mean age 22 ± 2.5 yrs, height 170.2 ± 8.2 cm, mass 76.3 ± 21.9 kg) underwent a baseline Ober's test to measure hip adduction ROM prior to the FR and control conditions. Subjects rolled the lateral portion of each thigh for 3 bouts of 20 seconds. A tempo of 3 seconds down and 3 seconds up the leg was maintained across FR bouts. A 5-minute walk served as the control condition. The Ober's test was repeated at less than 1 minute, 3 minutes, 10 minutes, 15 minutes, and 20 minutes following the FR bouts and the control to assess changes in hip adduction ROM over time. A blinded clinician conducted the Ober's test. A two-way analysis of variance was used to assess differences by condition and time. # Results No differences in hip adduction ROM were found at baseline between FR and CON within subjects (27.9 cm ± 7.5 vs. 27.7 cm ± 6.6, *p* > .05). Ober's test ROM was significantly greater in FR compared to CON immediately post-treatment (24.2 cm ± 6.3 vs. 28.2 cm ± 6.3, *p* = .00, *d* = .59), and 3 minutes post (24.6 cm ± 7.6 vs. 28.3 cm ± 5.9, *p* = .00, *d* = .56). No differences were observed 10 minutes post, 15 minutes post, or 20 minutes post FR or CON (*p* > .05). # Discussion Compared to walking, FR the IT band significantly increased hip adduction ROM as measured by the Ober's test. These increases appear to dissipate between 3 and 10 minutes post-FR. # Conclusion An acute bout of 3 sets of 20 seconds of FR may be effective for transiently increasing ROM. Whether these short-term increases have implications for chronic flexibility changes is unclear. # Level of evidence 2